Determination of Hexavalent Chromium (Cr(VI)) Concentrations via Ion Chromatography and UV-Vis Spectrophotometry in Samples Collected from Nacogdoches Wastewater Treatment Plant, East Texas (USA). (18th February 2016) - Onchoke, Kefa K.; Sasu, Salomey A.
Abstract : The concentration of hexavalent chromium (Cr(VI)), a toxic environmental pollutant and carcinogen, was determined in samples collected from Nacogdoches Wastewater Treatment Plant (NWWTP) using ion chromatography and UV-visible spectrophotometry (IC, UV-Vis). On reaction with 1, 5-diphenylcarbazide (DPC) Cr +6 forms a 1, 5-diphenylcarbazide-Cr(VI) complex, which is then analyzed at 530 nm and 540 nm, respectively. Via ion chromatography Cr(VI) concentrations were in the range of0.00190 ± 0.0020 and0.0010 ± 0.0006  ppm at the influent and effluent, respectively. With the use of standard addition wastewater samples were spiked with a 0.5 ppm Cr(VI) standard of various amounts and subsequently analyzed with UV-Vis spectrophotometry. The spiked concentrations gave Cr(VI) concentrations in the range of0.0090 ± 0.0060  ppm and0.0040 ± 0.0061  ppm at the influent and influent wastewater, respectively. The determined Cr(VI) concentrations through the ion chromatography and UV-Vis spectrophotometry are below the maximum USEPA contaminant concentration of 0.1 ppm. From the analysis, the NWWTP efficiently removes Cr(VI) before discharge into the environment through La Nana Creek. The removal efficiency for Cr(VI) was determined to be ≥92.8% along the wastewater treatment stages from the influent (aeration stage) to the effluent stages prior to discharge into the La Nana Creek.